2012
DOI: 10.1111/jdv.12004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of systemic methotrexate vs. acitretin in psoriasis patients with significant palmoplantar involvement: a prospective, randomized study

Abstract: Methotrexate is relatively inexpensive, safe and efficacious drug for the treatment of psoriasis patients with significant palmoplantar involvement. Acitretin can be used as an alternative therapy and with a good safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Alitretinoin is usually well-tolerated but sometimes headaches or flushing is problematic. Acitretin is another retinoid which is approved for the treatment of plaque psoriasis and is very effective for palmoplantar psoriasis (6). A previous open-label study suggested that acitretin could improve mild-to-moderate CHD (7).…”
Section: Introductionmentioning
confidence: 99%
“…Alitretinoin is usually well-tolerated but sometimes headaches or flushing is problematic. Acitretin is another retinoid which is approved for the treatment of plaque psoriasis and is very effective for palmoplantar psoriasis (6). A previous open-label study suggested that acitretin could improve mild-to-moderate CHD (7).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in this study, acitretin effectiveness could be negatively affected by the palmoplantar localization that was observed in about half of patient population. Indeed, a recent head‐to‐head study published in 2013 on a small cohort of patients, showed a reduced acitretin efficacy vs. methotrexate in treating plaque psoriasis with palmoplantar localization (Janagond, Kanwar, & Handa, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has limited response to standard agents as MTX, cyclosporine and acitretin [15]. The observed effect of NS in this type of psoriasis may indicate that the ointment has the ability to penetrate the thick epidermis of the palms and soles and exerts its effect in these sites.…”
Section: Discussionmentioning
confidence: 99%